Qualitative detection: Adulterants and preservatives in raw vis-Ã -vis packaged milk marketed in and around Guwahati city - Kakati, Smita; Talukdar, Archana; Hazarika, Razibuddinahmed; Raquib, Masuk; Laskar, Saurabh (Indian Journal of Animal Production and Management, 2018)
An investigation was carried out to monitor the presence of adulterants and preservatives of raw pooled milkvis-a-vis pasteurized packaged milk sold in and around Guwahati city. A total 200 raw pooled milk samplesand 5 branded pasteurized packaged milk samples were randomly collected to qualitatively determine thepresence of various adulterants and preservatives. The results of present study revealed that the percentadulteration of different adulterants and preservative in raw pooled milk, it was 11, 9, 6 and 2%for thepresence of water, neutralizers, salt and ammonia, respectively. None of the samples were positive forpresence of other adulterants and preservatives such as starch, cane sugar, cereal flour, glucose, hydrogenperoxide, urea and formalin. The study indicates that there is trend of adulteration of raw milk sold withcheaper and easily available ingredients in different parts of Guwahati city thereby affecting the nutritivevalue of milk and may be a concern of public health.